ANEMIA IN PREGNANT WOMEN OF EASTERN SUDAN - Adam, Ishag; Elghazali, Gehad; Idris Elbashir, Mustafa (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
It has been estimated that over half of all women in the world experience anemia during pregnancy with 95% occurring among women in the developing counteries1. Many risk factors for anemia were identified in pregnancy 2. In a community-based study we have recently reported that around 26% of the women of Eastern Sudan were anaemic, as well as we have shown that anaemia is one of the risk factors for deep venous thrombosis in the Sudanese pregnant women 3,4. However no proper published data exist for anaemia, its epidemiology and the risk factors during pregnancy in Sudan.   We performed a prospective study to estimate the incidence, timing and the risk factors for anemia during pregnancy in a population of Sudanese women in Eastern Sudan. Pregnant women attended antenatal care clinic at New Halfa Teaching Hospital were approached for participation in the study during September- November 2003. After a verbal consent a fixed questionnaire containing sociodemographic characters, obstetrical history as well as the known risk factors for anemia was filled (history of abortion, lack of iron supplementation, oral contraceptive pills (OCP) use and pica). All patients were examined clinically to detect signs of anemia–if present. Spleen was palpated and the gestational age was confirmed by Ultrasound in cases of discrepancy. Hemoglobin was estimated by colorimeter (WPA, U.K) and blood films for malaria were prepared using Geimsa stain. A well-trained technician who was blinded about the women’s data did the laboratory investigations. Data was entered in microcomputer using SPSS for windows the students, t -test, compared the mean ± SD of the age, gestational age, and hemoglobin. Relative risk was calculated for the possible factors. P < 0.05 was considered significant.